1991
DOI: 10.3758/bf03342678
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory and source monitoring

Abstract: This study demonstrates a manipulation that has opposite effects on old/new recognition and source monitoring. Deep processing of target items improved performance on an old/new recognition test in which subjects were to discriminate between targets and new distractors, but it impaired performance on a source monitoring test in which subjects were to discriminate between targets and distractors that had also been deeply processed during the experimental session. We argue that the relationship between old/new r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Cohen & Faulkner, 1989;Dywan & Jacoby, 1990;Dywan, Segalowitz, & Williamson, 1994;Ferguson et al, 1992;Hashtroudi et al, 1989;Mclntyre & Craik, 1987;Schacter, Kaszniak, Kihlstrom, & Valdiserri, 1991;Spencer & Raz, 1995). Such studies show that age-related source deficits are not just a function of an overall decline in memory and are consistent with the idea that although old-new recognition and source monitoring are related, they often rely on different memory features and judgment processes Johnson, Kounios, & Nolde, 1996;Lindsay & Johnson, 1989; see also Jacoby, Kelley, Brown, & Jasechko, 1989).…”
Section: The Source Monitoring Framework and Agingsupporting
confidence: 55%
See 1 more Smart Citation
“…Cohen & Faulkner, 1989;Dywan & Jacoby, 1990;Dywan, Segalowitz, & Williamson, 1994;Ferguson et al, 1992;Hashtroudi et al, 1989;Mclntyre & Craik, 1987;Schacter, Kaszniak, Kihlstrom, & Valdiserri, 1991;Spencer & Raz, 1995). Such studies show that age-related source deficits are not just a function of an overall decline in memory and are consistent with the idea that although old-new recognition and source monitoring are related, they often rely on different memory features and judgment processes Johnson, Kounios, & Nolde, 1996;Lindsay & Johnson, 1989; see also Jacoby, Kelley, Brown, & Jasechko, 1989).…”
Section: The Source Monitoring Framework and Agingsupporting
confidence: 55%
“…However, in the current study, the MCQ ratings were made separately after all source judgments were complete and thus could not have influenced source accuracy. (For other results showing the beneficial effect of more specific source evaluation, see Dodson & Johnson, 1993;Lindsay & Johnson, 1989;Multhaup, 1995;Zaragoza & Lane, 1994.) Presumably, weighting features and setting such criteria appropriately for a given task involves frontal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether one attends to particular features of an item is more a function of one's goals than of the item or its source. In fact, other work has shown that orienting tasks that increase item memory do not necessarily increase source monitoring accuracy (Johnson, Nolde, & DeLeonardis, 1996;Lindsay & Johnson, 1989), which suggests that focusing attention on particular features of an event does not necessarily provide reliable cues as to the source of the event.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lindsay and Johnson (1991) presented word pairs and asked individuals either to form a sentence using both words (deep-deep condition) or to form a sentence using the left word and to perform a shallow task on the right word (deep-shallow condition). An item-source tradeoff effect was observed: Item recognition for words presented on the right was better in the deep-deep condition than in the deepshallow condition, whereas source memory performance (i.e., determining whether a word was presented on the left or the right) was better in the deep-shallow condition than in the deep-deep condition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, item memory may depend more on semantic detail and on cognitive operations that influence item strength or item familiarity. Thus, the source-monitoring framework can be employed to explain a variety ofmemory phenomena (see Conway & Dewhurst, 1995;Hockley & Cristi, 1996;Lindsay & Johnson, 1991;Zaragoza & Lane, 1994).…”
mentioning
confidence: 99%